Vitamin C Administration Method On Osteoblast Healing In Rats Femur Bone - Sri Lestari Ramadhani Nasution; Muhammad Ari Pratama; Muhammad Faridz Syahrian (INFOKUM, 2025)
Bone, as an important organ in the body, has a fundamental role in supporting biomechanical functions, carrying out the hematopoiesis process, and maintaining calcium homeostasis. The cellular components of bone involve various types of cells, including osteogenic precursor cells, osteoblasts, osteoclasts, osteocytes, and hematopoietic elements from the bone marrow. Vitamin C, or ascorbic acid, is a water-soluble vitamin that plays an important role in the formation of collagen, skin, tendons, ligaments, blood vessels, as well as in wound healing and maintenance of cartilage, bones, and teeth. This study aims to analysed mean value and difference in the number of osteoblast cells in the femur of rats exposed to alcohol between groups receiving vitamin C. Based on the results of the One Way ANOVA test, the p value = 0.018 <0.05 was obtained, which indicated a significant difference in the average osteoblasts between groups. Furthermore, in the Post Hoc test, a difference in the mean osteoblasts was found between groups T3 and T5 with a p value = 0.029 < 0.05 and between groups T4 and T5 with a p value = 0.044 < 0.05. Conclusion: Administration of vitamin C can affect the increase in the number of osteoblast cells in the bone healing process in mice exposed to alcohol.